(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
A new subspecies, viz. Dimeria hohenackeri Hochst. ex Miq. subsp. kodaguensis Kiran Raj, Sivad. & Dileep from South Karnataka of the Southern Western Ghats in Peninsular India is described and illustrated. It mainly differs from D. hohenackeri Hochst. ex Miq. subsp. hohenackeri in having mat-forming habit with leaves crowded at culm-base, spikelets 34 mm long and glumes not widely divergent during anthesis. Bangladesh J. Plant Taxon. 23(1): 27-31, 2016 (June)